The outlook of the Malaysian banking sector beyond 2000: A study on the role taken by Bumiputra-Commerce Bank Berhad / Suhardi Razali - Razali, Suhardi (2002)
In a speech delivered at the 4th L a n g k a w i International Dialogue on July 2 5, 1999, our Prime Minister, Datuk Dr Seri Dr Mahathir bin Mohamad spoke, “ There is no doubt that while globalization is an idea whose time has come and one that all nations must be prepared to accept, there are lingering perils, since globalization will not be played on a level field”. Indeed, the ability to reap the benefits arising from greater competition depends largely on the capability and capacity of our financial institutions to adapt swiftly and to embrace the changes. Can w e( w i t h the u n 1 e v e 1 e d competition!) This paper is written to understand this bewildering issue. The writer’s opinion is that we must address the issue in a total concerted effort rather than as an exclusive business decision. Both the private and public sectors must work closely with each other to pave the way for a better survival of the nation’s economy as advocated by our Prime Minister. He quoted in his speech at the 1st Southern Africa International Dialogue in Botswana on 5111 May 1997, “ Under the Malaysia